2006
DOI: 10.1075/sibil.31.05gal
|View full text |Cite
|
Sign up to set email alerts
|

Age and native language influence on the perception of English vowels

Abstract: This paper examines, within the framework of Flege’s speech learning model (SLM), the relevance of two factors – age and native language – for the acquisition align of vowel perception abilities by young Spanish learners of English in a formal instructional environment. Findings indicate that age did influence the participants’ ability to identify English vowels, but not in the expected direction and only for those vowels considered to be identical. Thus, the results do not provide evidence of the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Historically, pronunciation has been overlooked compared to other skills in formal learning contexts, characterized by limited exposure in conventional language teaching and the presence of non-native speaker accents among educators (Gallardo-del-Puerto et al, 2006). Given that CLIL contexts provide added exposure, it becomes interesting to explore pronunciation in these contexts.…”
Section: Motivation Towards L2 English Pronunciation: the Role Of Ins...mentioning
confidence: 99%
“…Historically, pronunciation has been overlooked compared to other skills in formal learning contexts, characterized by limited exposure in conventional language teaching and the presence of non-native speaker accents among educators (Gallardo-del-Puerto et al, 2006). Given that CLIL contexts provide added exposure, it becomes interesting to explore pronunciation in these contexts.…”
Section: Motivation Towards L2 English Pronunciation: the Role Of Ins...mentioning
confidence: 99%
“…Research on metalinguistic knowledge about source languages (typically the L1) and more specifically its relation to language transfer is scarce. While metalinguistic knowledge concerning the source language(s) is occasionally invoked as an explanation for the presence or absence of transfer (e.g., Cenoz, 2001;Gallardo del Puerto, García Lecumberri, & Cenoz, 2006;Odlin, 1990;Vanhove, 2017; see also Ringbom's [2007] prediction about the utility of L2 Finnish in learning Swahili), this explanation is rarely put to the test. To my knowledge, the only exception is a study by Falk, Lindqvist, and Bardel (2015), who investigated the relationship between L1 Swedish explicit metalinguistic knowledge and L3 Dutch adjective placement and found that better performance on the L1 metalinguistic test was associated with more accurate L3 adjective placement.…”
Section: Lack Of Metalinguistic Knowledge As a Possible Explanation For Non-transfermentioning
confidence: 99%